An assessment of mining company housing policies: Northern Cape Cases - Tshuma, Rachel (My University, 2022)
Mining towns are challenged with housing issues for miners, the development of informal settlements in surrounding towns and inadequate infrastructure to accommodate the influx of migrant mine labourers. This research reports on the challenges of housing for mine workers in the John Taolo Gaetsewe and ZF Mgcawu District Municipalities. It provides an assessment of mining company housing policies which outline various housing options against the UNHabitat elements of adequate housing. The options include a homeownership subsidy, rental options, and housing allowance. A qualitative study was undertaken, through semi-structured interviews with the local municipalities, private planning consultants, local community organisations and unions. Findings indicated that housing is a major challenge within the study area, from an availability and affordability perspective. High demand for housing resulted in extremely high property prices, presenting a challenge for low-income earners. The assessment indicated the housing options have varying adequacy depending on finances, worker place of origin or even their preferences as individuals with or without families.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Urban Studies (Housing and Human Settlements) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2022